Étude du paysage à travers sa composante bâtie - Fabian de Smet (Projets de Paysage)
Through various morphological studies, this doctoral research has validated the hypothesis of a typology of constructions set for the description of the built-up component of the suburban landscape. This article relates the development of this typology.